Perubahan Konstitusi Dan Implikasinya Pada Perubahan Lembaga Negara - Frinaldi, Aldri; S, Nurman (Jurnal Demokrasi, 2005)
The Amendment of UUD 1945 at reform era have brought implication happened change to high institute structure of state. The change influenced by existence of the change of political constellation and political power in Indonesia. Because, constitution influenced by will political from top kick political power at one particular state. By normative- juridical, having implication is existence of change authority had previous Institute State, and there is also Institute new State emerges. By political-sociological, change the constitution influenced by existence of change political constellation and political power in Indonesia Kata Kunci: Konstitusi, Amandemen, Lembaga Negara Â